The reporting guideline of animal studies---ARRIVE 2019 - Zhi-Zhong SHANG; Yan-Biao JIANG; Bing ZHAO; Zhe-Wen ZHANG; Fei ZHAO; Ting ZHANG; Jun-Hua ZHANG; Bin MA (Yixue xinzhi zazhi)
As a tool to improve the reporting quality of animal studies, ARRIVE guidelines have been recognized by many experts. However, limited to partial items are too tedious and the reasons for the lack of clear priorities for each item, it leads to barriers while the researchers try to use it in practice. Therefore, guide development experts re-revised the ARRIVE guide and published ARRIVE 2019. In this paper, ARRIVE 2019 was interpreted in detail in order to make full use of ARRIVE guidelines to improve the design, implementation and reporting of animal studies, and to improve the reproducibility of animal studies and the reproducibility of results.